Boom. Tick. Bing! Writing Bodies In. (LEARNing Landscapes, 2010)
This paper describes a poetic response to the school-based practicum for beginning secondary teachers. Following their first practicum experience, in their English Method class back at the university, students pooled sensory details and memories of the week they had just spent in schools to write their own poems.The paper includes one of the poems and some thoughts about the complexity, ambivalence and embodied knowing that poetry opens up space for in reflecting on initial school experiences for beginning teachers.
Keywords: poetic response; secondary teachers; school-based practicum; poetry; school experience; begining teacher